Effectiveness of omalizumab in patients with severe allergic asthma: A retrospective study in China. (September 2021) - Zhang, Min; Jin, Meiling; Zhou, Xin; Lin, Jiangtao; Liu, Xiansheng; Liu, Chuntao; Huang, Mao; Wang, Wen; Chen, Liang; Huang, Yijiang; Li, Jing; Zhang, Qingling; et al.
Abstract: Background: We conducted the first real-world study of treatment with omalizumab, a humanized monoclonal anti-immunoglobulin E antibody, in Chinese patients with severe allergic asthma. Objective: The primary objective was the steroid-sparing effect of omalizumab after 12 and 16 weeks of treatment. Characteristics of the patient population, treatment patterns, response rate, and other measures of therapeutic effectiveness were also reported. Methods: This nationwide, retrospective, real-world study was conducted in patients with severe allergic asthma who were treated with omalizumab in China. Data, including demographics, Asthma Control Test (ACT) and laboratory and lung function test results, and omalizumab use information, were extracted from patient records collected as part of a previously conducted real-world survey (Asthma Group of the Respiratory Disease Society of the Chinese Medical Association). Results: In total, 139 patient records were included; 131 and 118 patients remained on treatment at the ≥12- and ≥16-week time points, respectively. The mean ± standard deviation age and median asthma duration (interquartile range) were 47.4 ± 14.3 and 7 (4, 15) years, respectively; 75.6% of patients had a history of allergic disease. Reductions (versus baseline) in inhaled corticosteroid/long-acting β2 agonists or oral corticosteroids were reported in 61.1% and 63.6% of patients at ≥12 and ≥ 16 weeks, respectively. There were significant improvements in ACT scores (6.08, P < .001) and nitric oxide fraction in exhaled air (−13.0, P = .01) from baseline. Multivariate analysis revealed that age and allergic medical history were predictors of omalizumab treatment response. No serious adverse events were reported. Conclusion: Real-world omalizumab treatment was efficacious and well-tolerated in Chinese patients with severe allergic asthma. Highlights: In real world, omalizumab provided a steroid-sparing effect with >60% patients reducing ICS/LABA or OCS after 16 weeks. Omalizumab was highly effective and well tolerated, with a significant improvement in asthma attacks in Chinese patients. Multivariate analysis revealed that age and allergic medical history were predictors of omalizumab treatment response.